Relationship between the clinical outcomes and the systemic inflammatory response index and systemic immune inflammation index after total knee arthroplasty - Kürüm, H.; Key, S.; Tosun, H.B.; Yılmaz, E.; Kürüm, K.O.; İpekten, F.; Akcan, A. (Springer Nature, 2024)
Background: Periprosthetic joint infection (PJI) is an extremely damaging complication that can occur after total knee arthroplasty (TKA). There is no study in the literature investigating the relationship between systemic inflammatory response index (SIRI) and systemic inflammation immune index (SII) values and prognosis and infection in patients who have undergone TKA. The aim of the study was to determine the relationship between the inflammatory index values and the rate of PJI in patients who had previously had TKA. Methods: A total of 187 patients who underwent TKA between 2015 and 2023 years were retrospectively analyzed. Results: The median value of the postoperative SII index was 1862.3 (1146.6–2630.4) in the infected group, while it was 1058.2 (605.0–1762.8) in the non-infected group (p < 0.001). In the infected group, the median value of preoperative SIRI was observed as 2.3 (1.7–3.5), while in the non-infected group it was 0.9 (0.7–1.5) (p < 0.001). The cutoff value for postoperative SIRI was observed to be 2.19, with a sensitivity value of 95%, a specificity value of 46%, the AUC value observed was 65%. The cutoff value for the postoperative SII index was observed to be 1058.96, with a sensitivity value of 100%, a specificity value of 50%. Conclusions: Our study has associated the inflammatory markers SIRI, SII, neutrophil lymphocyte ratio, and platelet lymphocyte ratio with PJI, which are easy and inexpensive to obtain. There is no widely recognized serum biomarker that can be used alone with good sensitivity and specificity. This study contributes to finding the gold standard inflammatory marker for diagnosing PJI. © The Author(s), under exclusive licence to Istituto Ortopedico Rizzoli 2024.
Keywords: Periprosthetic joint infection; Systemic inflammation immune index; Systemic inflammatory response index; Total knee arthroplasty